The calling from the margins : mission to and by hearing-impaired people in francophone churches in Pretoria and Johannesburg - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.